Coronary Intravascular Lithotripsy in Clinical Practice - Takashi Ashikaga; Toshihiro Nozato; Yasutoshi Nagata; Tetsumin Lee; Masakazu Kaneko; Toru Misawa; Masashi Nagase; Mao Matsuyama; Daigo Kachi; Maki Ohira; Kazuki Matsuda; Tomoki Horie (Journal of Clinical Medicine, 2026)
The presence of coronary artery calcification is associated with lower procedural success rates and worse long-term clinical outcomes. Atherectomy devices, such as rotational atherectomy (RA), orbital atherectomy (OA), and excimer laser coronary atherectomy (ELCA), have been used as preparation devices for severely calcified lesions. Intravascular lithotripsy (IVL) has recently been used to safely and selectively disrupt calcified coronary lesions. It produces acoustic shockwaves, which interact with the coronary calcium to create multiplanar fractures. These calcium fractures increase vessel compliance and result in a desirable minimal stent area or the ability to finish with a drug-coated balloon (DCB) alone strategy. The IVL has established its safety and efficacy for calcified lesions and its advantages over atherectomy devices include ease of use on a workhorse wire, ability to modify deep calcium, and less debris embolization causing slow-flow or no-reflow. A combined strategy of atherectomy devices followed by IVL may be efficient. We describe our experience with IVL and procedural technique in our catheterization laboratory.